Air pollution and labour productivity: firm-level spatial evidence from China - Yi Zhang; Weijun Liang; Yongfu Liang (Environmental Research Communications)
As environmental degradation increasingly threatens sustainable growth, understanding the impact of air pollution on firm performance has become a critical area of research. This study investigates the influence of delicate particulate matter (PM _1 ) on labour productivity, utilising firm-level data from Chinese A-share listed companies and employing spatial econometric models alongside a bespoke firm-level spatial weight matrix. To address endogeneity issues, the temperature inversion variable is instrumental in ascertaining the causal effect of PM _1 pollution. The findings indicate that PM _1 significantly diminishes labour productivity in the affected firms, generating detrimental spatial spillover effects on neighbouring firms Additionally, further analysis of heterogeneity demonstrates that state-owned and labour-intensive enterprises exhibit reduced susceptibility to pollution shocks. In contrast, non-state-owned, technology-intensive, and capital-intensive firms experience more substantial losses in labour productivity. These insights emphasise the necessity to customise environmental policies and industrial support measures according to the distinctive characteristics of individual firms.